2014
DOI: 10.1177/1753425913516885
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of the endotoxin activity assay as a biomarker to assess the severity of endotoxemia in critically ill patients

Abstract: The aim of this study was to investigate the prevalence of endotoxemia in critically ill Japanese patients using the endotoxin activity assay, a newly developed rapid assay of endotoxin. The endotoxin levels (EA levels) in the blood of 314 patients admitted to our university hospital's intensive care unit (ICU) were measured within 24 h of admission, and its correlation with disease severity and outcome examined. In addition, the EA levels in 61 samples from healthy volunteers were measured. EA level was 0.39 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 12 publications
1
18
0
1
Order By: Relevance
“…These results are in agreement with earlier studies, which showed that endotoxemia was related to disease severity, the SOFA score, a higher plasma lactate concentration, lower systemic vascular resistance, depressed ejection fractions, a greater need for vasopressors, and a greater risk of dying (35)(36)(37). Thus, it can be anticipated that LPS measurement by HPLC/MS/MS could become a promising tool in the diagnosis, follow-up, and therapeutic management of patients with sepsis.…”
Section: Discussionsupporting
confidence: 81%
“…These results are in agreement with earlier studies, which showed that endotoxemia was related to disease severity, the SOFA score, a higher plasma lactate concentration, lower systemic vascular resistance, depressed ejection fractions, a greater need for vasopressors, and a greater risk of dying (35)(36)(37). Thus, it can be anticipated that LPS measurement by HPLC/MS/MS could become a promising tool in the diagnosis, follow-up, and therapeutic management of patients with sepsis.…”
Section: Discussionsupporting
confidence: 81%
“…Endotoxin activity is expressed in relative units derived from the integral of the basal and stimulated chemiluminescent response (on a scale from 0 to 1). Most of the EA levels of healthy controls are <0.2, with 72% being <0.1, and 16% being between 0.1 and 0.2 . An EA level of 0.4 is approximately equivalent to an endotoxin concentration of 25–50 pg/mL, and a level of 0.6 is approximately equivalent to a lipopolysaccharide concentration of 100–200 pg/mL.…”
Section: Methodsmentioning
confidence: 99%
“…These biological effects include affecting the structures and functions of cells and organs, raising body temperature, triggering the coagulation cascade, altering metabolic functions, and causing hemodynamic shock (Yamamoto et al 2002). Serious endotoxin intoxication will cause endotoxemia (Ikeda et al 2014). Because of its toxicity, removing endotoxin from drugs and food is of great importance.…”
Section: Introductionmentioning
confidence: 99%